PERMASALAHAN PENYEDIAAN RUANG TERBUKA NON HIJAU PADA PERKOTAAN SLEMAN STUDI KASUS KECAMATAN DEPOK - Sarweswara, Arga Prihandana; Dwi Pramono, Retno Widodo (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Human activity is closely related to open spaces. Non-green open space (RTNH) is a form of public open space that has social, cultural, and environmental conservation functions. The lack of RTNH in the urban area of Sleman, especially in Depok District, occurs due to very high population density and development that is considered very impulsive. The research method used in this research uses critical thinking, using secondary data that is processed and matched with conditions in the field. The results of this study obtained that the high level of development was one of them caused by government programs related to the Fast Growing Strategic Area (KSCT). The overlapping policies make it impossible to make a clear reference to the direction of development in the urban area of Sleman. Therefore, coordination between the central government and local governments is needed in formulating regulations related to RTNH and community synergy so that their implementation is effective.